Exploring Technological Factors and Cloud Accounting Adoption in MSMEs: A Comprehensive TAM Framework - Musyaffi, Ayatulloh Michael; Johari, Razana Juhaida; Hendrayati, Heny; Wolor, Christian Wiradendi; Armeliza, Diah; Mukhibad, Hasan; Izwandi, Hafiz Surya Chandra (International Review of Management and Marketing, 2024)
The adoption of cloud accounting technology among micro, small, and medium enterprises (MSMEs) is becoming increasingly vital for enhancing corporate efficiency and sustainability. However, the adoption rate requires enhancement due to several obstacles, including insufficient digital literacy (DLC) and technological complexity (CX). This study aims to identify the factors influencing the adoption of cloud accounting in MSMEs using TAM framework. This research encompassed 307 participants from MSMEs in Indonesia, with data gathered via surveys and analyzed with the Structural Equation Model—Partial Least Squares (SEM-PLS). DLC and compatibility (CO) substantially affect the perceived ease of use (PE) and usefulness (PU) of cloud accounting technology. Meanwhile, relative advantage (RA) positively impacts PE but does not significantly influence PU. CX greatly influenced users’ intention (INT) to embrace cloud accounting. These findings highlights the crucial role of TAM and indicate that enhancing DLC and CO alongside current business practices is essential to promoting technology adoption. This study provides practical recommendations for policymakers and technology providers to improve the use of digital technologies among MSMEs.